Oxygen versus Reactive Oxygen in the Regulation of HIF-1α: The Balance Tips - Thilo Hagen (Biochemistry Research International)
Hypoxia inducible factor (HIF) is known as the master regulator of the cellular response to hypoxia and is of pivotal importance during development as well as in human disease, particularly in cancer. It is composed of a constitutively expressed β subunit (HIF-1β) and an oxygen-regulated α subunit (HIF-1α and HIF-2α), whose stability is tightly controlled by a family of oxygen- and iron-dependent prolyl hydroxylase enzymes. Whether or not mitochondria-derived reactive oxygen species (ROS) are involved in the regulation of Hypoxia Inducible Factor-1α has been a matter of contention for the last 10 years, with equally compelling evidence in favor and against their contribution. A number of recent papers appear to tip the balance against a role for ROS. Thus, it has been demonstrated that HIF prolyl hydroxylases are unlikely to be physiological targets of ROS and that the increase in ROS that is associated with downregulation of Thioredoxin Reductase in hypoxia does not affect HIF-1α stabilization. Finally, the protein CHCHD4, which modulates cellular HIF-1α concentrations by promoting mitochondrial electron transport chain activity, has been proposed to exert its regulatory effect by affecting cellular oxygen availability. These reports are consistent with the hypothesis that mitochondria play a critical role in the regulation of HIF-1α by controlling intracellular oxygen concentrations.